Cellular and Transcriptional Responses of Crassostrea gigas Hemocytes Exposed in Vitro to Brevetoxin (PbTx-2) - Danielle F. Mello; Eliza S. De Oliveira; Renato C. Vieira; Erik Simoes; Rafael Trevisan; Alcir Luiz Dafre; Margherita Anna Barracco (Marine Drugs, 2012)
Hemocytes mediate a series of immune reactions essential for bivalve survival in the environment, however, the impact of harmful algal species and their associated phycotoxins upon bivalve immune system is under debate. To better understand the possible toxic effects of these toxins, Crassostrea gigas hemocytes were exposed to brevetoxin (PbTx-2). Hemocyte viability, monitored through the neutral red retention and MTT reduction assays, and apoptosis (Hoechst staining) remained unchanged during 12 h of exposure to PbTx-2 in concentrations up to 1000 µg/L. Despite cell viability and apoptosis remained stable, hemocytes incubated for 4 h with 1000 µg/L of PbTx-2 revealed higher expression levels of Hsp70 (p < 0.01) and CYP356A1 ( p < 0.05) transcripts and a tendency to increase FABP expression, as evaluated by Real-Time quantitative PCR. The expression of other studied genes (BPI, IL-17, GSTO, EcSOD, Prx6, SOD and GPx) remained unchanged. The results suggest that the absence of cytotoxic effects of PbTx-2 in Crassostrea gigas hemocytes, even at high concentrations, allow early defense responses to be produced by activating protective mechanisms associated to detoxification (CYP356A1 and possibly FABP) and stress (Hsp70), but not to immune or to antioxidant (BPI, IL-17, EcSOD, Prx6, GPx and SOD) related genes.